" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
x-y=0
2x=0
x-y=10
2x=0
-y=10-x / *2
2x=0
-2y=20-2x
2x=0
-2y=20-0
2x=0
-2y=20-0 / : (-2)
y=10
x=0
8x-6y=10
7x-y=5
8x-6y=10
-y=5-7x
8x-6y=10
y=-5+7x
8x-6(-5+7x)=10
y=-5+7x
8x+30 -42x=10
y=-5+7x
-34x=-20 34x=20 / :34 x=¹⁰/₁₇
x=10/17
y=-5+7(10/17)
x=10/17
y=-5+70/17
x=10/17
y=-85/17+70/17
x=10/17
y=-15/17
12p-7r=-16
p-3r=-69
12p-7r=-16
p=69+3r
12(69+3r)-7r=-16
p=69+3r
828+36r-7r=-16
p=69+3r
29r=-16-828
p=69+3r
29r=-846 r=-846/29
p=69+3(-846/29)
r=-846/29
p=2001/29+(-2538/29
r=-29 ⁵/₂₉
p= -537/29 p=-18 ¹⁵/₂₉
11k+17l=45
13k+l=15
11k+17l=45
l=15-13k
11k+17(15-13k)=45
l=15-13k
11k+255-221k=45
l=15-13k
210k=45-255 210k=-210 k= -1
k=-1
l=15-13(-1)
k=-1
l=15+13
k=-1
l=28
8a+9b=36
a-16b=210
8a+9b=36
a=210+16b
8(210+16b)+9b=36
a=210+16b
1680+128b+9b=36
a=210+16b
137b=36-1680
a=210+16b
137b=-1644 b= -12
a=210+16(-12)
b=-12
a=210-192
b=-12
a=18
6a-21b=228
a-12b=21
6a-21b=228
a=21-12b
6(21-12b)-21b=228
a=21-12b
126-72b=228
a=21-12b
-72b=228-126 -72b=102:(-72)
a=21-12b
b=-102/72
a=21-12(-102/72)
b=-102/72
a=1512/72+1224/72
b=-102/72
a=2736/72
b=- 1¹⁵/₃₆
a=38
x-y=10
2x=0/:2
x-y=10
x=0
0-y=10
x=0
-y=10/*(-1)
x=0
y=-10
b)8x-6y=10
7x+y=5/*6
8x-6y=10
42x+6y=30
50x=40/:50
x=0,8
8x-6y=10
x=0,8
8*0,8-6y=10
x=0,8
6,4-6y=10
x=0,8
-6y=10-6,4
x=0,8
-6y=3,6/:(-6)
x=0,8
y=-0,6
x=0,8
c)12p-7r=-16
p-3r=-69
12p-7r=-16
p=-69+3r
12(-69+3r)-7r=-16
p=-69+3r
-828+36r-7r=-16
p=-69+3r
29r=-16+828
p=-69+3r
29r=812/:29
p=-69+3r
r=28
p=-69+3r
r=28
p=-69+3*28
r=28
p=-69+84
r=28
p=15
d)11k+17l=45
13k+l=15
11k+17l=45
l=15-13k
11k+17(15-13k)=45
l=15-13k
11k+255-221k=45
l=15-13k
11k-221k=45-255
l=15-13k
-210k=-210/:(-210)
l=15-13k
k=1
l=15-13*1
k=1
l=15-13
k=1
l=2
e)8a+9b=36
a-16b=210/*(-8)
8a+9b=36
-8a+128b=-1680
137b=-1644/:137
b=-12
8a+9b=36
b=-12
8a+9*(-12)=36
b=-12
8a-108=36
b=-12
8a=36+108
b=-12
8a=144/:8
b=-12
a=18
b=-12